The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/10410236.2019.1598740
|View full text |Cite
|
Sign up to set email alerts
|

Using Family Members as Medical Interpreters: An Explanation of Healthcare Practitioners’ Normative Practices in Pediatric and Neonatal Departments in Australia

Abstract: According to the Australian Bureau of Statistics (2016), both international tourism and migration of people with low English proficiency (LEP) to Australia are increasing. Thus, healthcare practitioners (HPs) increasingly use interpreters to communicate with patients with LEP. Although qualified interpreters are the most suggested and policy-endorsed mechanism for communicating with patients with LEP, family members (FMIs) are also used as interpreters.This study investigated a) when do health professionals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…(2017) Thematic and hermeneutic analysis n=1 (12.5%) Kynoe et al. (2020) Phenomenological analysis n=1 (12.5%) Stephen (2021) Thematic analysis n=1 (12.5%) Pines et al. (2020) Framework analysis n=1 (12.5%) Williams et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) Thematic and hermeneutic analysis n=1 (12.5%) Kynoe et al. (2020) Phenomenological analysis n=1 (12.5%) Stephen (2021) Thematic analysis n=1 (12.5%) Pines et al. (2020) Framework analysis n=1 (12.5%) Williams et al.…”
Section: Resultsmentioning
confidence: 99%
“… Awareness of guidelines on interpreter-use was highest amongst nurses. Pines et al. (2020) Australia To investigate (a) when healthcare professionals consider it appropriate to use family members as interpreters and (b) what characteristics of family members healthcare professionals believe make them suitable to act as interpreters.…”
Section: Methodsmentioning
confidence: 99%
“…Despite policies that state that qualified interpreters should normally be used, and free access to telephone interpreters in health consultations (Phillips, 2010), research suggests there is a significant underuse of qualified interpreters in police and health encounters (Atkin, 2008;Gray et al, 2011;Wakefield et al, 2015), with family members frequently used instead (Atkin, 2008;Pines et al, 2020) often because it is more convenient (Diamond et al, 2009). Gray et al (2011) found that family members were used in 49% -83% of general practice consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Family members or bilingual colleagues are often used to interpret in healthcare situations in lieu of a trained professional interpreter (Gray, Hilder, & Donaldson, 2011). Family members may be suitable in some aspects of healthcare translation (Hilder et al, 2017;Pines, Jones, & Sheeran, 2019); however, they are at risk of being exposed to highly sensitive information (Nielsen, Abdulkadir, Lynnerup, & Sodemann, 2019) and may not be able to adequately translate technical medico-legal phrases or words (Attard et al, 2015). There are similar challenges when bilingual colleagues are used (Ali & Johnson, 2017).…”
Section: Clear Communication Is An Essential Component Of Safe Andmentioning
confidence: 99%